2018
DOI: 10.1002/stc.2235
|View full text |Cite
|
Sign up to set email alerts
|

Vision‐based vibration monitoring using existing cameras installed within a building

Abstract: Summary A new methodology for the monitoring of dynamic characteristics of buildings has been proposed. It is based on digital image analysis leveraging pre‐existing cameras installed within a building, such as surveillance cameras. The method is used for real‐time measurement of interstory drifts, from which dynamic characteristics (e.g., fundamental period) can easily be extracted to detect damage to the structural system. It has applications particularly in the case of post‐earthquake damage estimation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…AI-based disaster management has attracted much interest from researchers and practitioners in earthquake engineering. This includes CV-based damage detection and quantification, [94][95][96] CV-based vibration extraction, 97,98 and rapid damage inference and condition assessment for a single structure and a large number of structures in a zone in an urban area. 99,100 Disaster management (e.g.…”
Section: Ai-based Disaster Managementmentioning
confidence: 99%
“…AI-based disaster management has attracted much interest from researchers and practitioners in earthquake engineering. This includes CV-based damage detection and quantification, [94][95][96] CV-based vibration extraction, 97,98 and rapid damage inference and condition assessment for a single structure and a large number of structures in a zone in an urban area. 99,100 Disaster management (e.g.…”
Section: Ai-based Disaster Managementmentioning
confidence: 99%
“…The results indicated that EEM was more accurate than orientation‐code‐matching, DIC, and SURF. Harvey and Elisha used existing surveillance cameras to monitor interstory drift. Additionally, many applications were introduced in the referenced review papers .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, some scholars have proposed SHM methods using image-based measurement techniques [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Image-based measurement methods have been widely used in various experimental mechanics studies.…”
Section: Introductionmentioning
confidence: 99%